67P Real-world outcomes for patients with recurrent/metastatic squamous cell carcinoma of the head and neck (R/M SCCHN) treated with nivolumab. (15th December 2019) - Singh, P; You, M; Lubinga, S; Zhang, Y
Abstract: Background: Checkmate 141, a phase III trial evaluating nivolumab versus standard of care in R/M SCCHN patients after platinum therapy showed a significant improvement in overall survival for nivolumab. This study presents real-world survival data of patients in the United States using nivolumab for head and neck cancer treatment. Methods: A retrospective data analysis was performed using the Flatiron Health's oncology electronic medical record (EMR) dataset. Data were used from April 2016 to July 2019 with an index date of nivolumab therapy start. Patients were eligible for the study if they were 18 years of age or older, received nivolumab after initial platinum-based therapy, and had at least one month of data after index date. Results: 368 patients met inclusion criteria for this study. Median age was 63.5 years with 79% males and 21% females. The majority of patients (81%) had a history of smoking and an ECOG status of 0 or 1 when reported (75%). The largest proportion of patients (47%) had a primary site of oropharynx, and 47% of patients who had an HPV test were positive. Median and mean follow up from nivolumab therapy start was 6.0 and 8.1 months, respectively. Median duration of treatment for patients receiving nivolumab was 2.3 months (IQR 1.2-5.6) with a median number of 6 doses (IQR 3-12). Most patients received nivolumab as either first-line (29%) or second-line (60%) treatment. The probability of survival at year 1 was 40% (SE 3%), with a median overall survival of 8.1 months (95% CI, 7.0 to 9.8). For the patients who received nivolumab as first-line treatment, 1-year survival probability was 56% (SE 5%) and median OS was 15.2 months (95% CI, 9.0 to 22.1). Conclusion: This real-world study of nivolumab in R/M SCCHN patients in the United States shows that the improved survival demonstrated by nivolumab in CheckMate 141 translates into similar real-world outcomes for patients, with an even greater benefit in first-line patients. These results are consistent with other observational analyses in Europe and reinforce the survival benefit of nivolumab in R/M SCCHN patients as early as first line. Legal entity responsible for the study: Bristol-Myers Squibb. Funding: Bristol-Myers Squibb. Disclosure: P. Singh: Full / Part-time employment: Bristol-Myers Squibb. M. You: Full / Part-time employment: Bristol-Myers Squibb. S. Lubinga: Shareholder / Stockholder / Stock options, Full / Part-time employment: Bristol-Myers Squibb. Y. Zhang: Shareholder / Stockholder / Stock options, Full / Part-time employment: Bristol-Myers Squibb.